A chatbot for teaching software testing CTFL syllabus - Teh, Wing Fung (2025)
Software testing is a vital process in software development, ensuring product quality by minimizing defects and preventing errors that affect usability. The ISTQB Certified Tester Foundation Level (CTFL) syllabus introduces fundamental concepts of software testing, serving as an important resource for students and lecturers. This project develops a web application with an integrated chatbot specifically designed to teach the CTFL syllabus. Developed using robust Laravel backend and React front end, integrating a large-language-model-driven chatbot to provide concise explanations, practical examples, and automatically generated quiz questions to reinforce user understanding. The development followed V-Model methodology, conducting different kind of testing including unit, integration, system, and user acceptance to ensure the web application to implement all the stated requirements from users, and to reinforce its core educational objectives through systematic validation. In the results of conducted testings, the web application is proven to have outstanding performance without defects affecting the usage. By combining natural language interaction with structured syllabus content, the system offers an engaging and accessible learning tool that enhances comprehension, supports teaching, and better prepares learners for CTFL certification and implement professional practice in the work field.